1997
DOI: 10.1136/jnnp.62.6.629
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ipsilateral motor cortex in mirror movements.

Abstract: The mechanism of mirror movements in two patients was investigated; one with congenital mirror movement, the other with schizencephaly. Transcranial magnetic stimulation on one side elicited motor evoked potentials (MEPs) in their thenar muscles on both sides with almost the same latencies, minimal thresholds, and cortical topographies. During voluntary contraction of the thenar muscle on one side, contralateral transcranial magnetic stimulation induced a silent period not only on the voluntary contraction sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 11 publications
1
18
0
2
Order By: Relevance
“…Although unaffected-side SM1 overactivation might reflect recruitment of the uncrossed corticospinal tract, its relation with mirror movements is still a matter of debate. [1][2][3][4][5]26,27 In our study, mirror movements were documented in patients 2 and 4 at PET1 and in patients 4 and 5 at PET2, but although patients 2 and 4 did show corresponding overactivations, patient 5 did not, and in addition, patient 2 still showed this overactivation despite the fact that his mirror movements had vanished. Thus, if a relationship between unaffected hemisphere SM1 overactivation and mirror movements exists, it does not appear to be systematic.…”
Section: Discussionmentioning
confidence: 71%
“…Although unaffected-side SM1 overactivation might reflect recruitment of the uncrossed corticospinal tract, its relation with mirror movements is still a matter of debate. [1][2][3][4][5]26,27 In our study, mirror movements were documented in patients 2 and 4 at PET1 and in patients 4 and 5 at PET2, but although patients 2 and 4 did show corresponding overactivations, patient 5 did not, and in addition, patient 2 still showed this overactivation despite the fact that his mirror movements had vanished. Thus, if a relationship between unaffected hemisphere SM1 overactivation and mirror movements exists, it does not appear to be systematic.…”
Section: Discussionmentioning
confidence: 71%
“…7,14 In some patients with primary MM syndromes, transcranial magnetic stimulation has disclosed an increased ipsilateral hand representation in the motor cortex of each hemisphere. 34 During a hand motor task by such subjects, PET studies have found contralateral 34 or bilateral 35 motor cortex activation. Together, these data suggest that MM after adult stroke may represent an exaggeration of the degree of bilateral motor representation normally seen in adults; some patients with cerebral palsy and primary MM may also have a different mechanism underlying MM.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, when people plan a complex sequence of unilateral movements (Verstynen and Ivry 2011) or a coordinated movement of the upper and lower limbs (van den Berg et al 2011), MEPs are larger in homologous muscles of the resting hand. This spillover may arise from interhemispheric connections between homologous muscles (Kanouchi et al 1997;Kobayashi et al 2003) or the engagement of bihemispheric planning processes (Cramer et al 1999;Hanakawa et al 2005;Shibasaki et al 1993;Verstynen et al 2005). Moreover, as the complexity of movement execution increases, greater inhibition may be required to uncouple the two hands (Meyer-Lindenberg et al 2002), with failures of this form of inhibition underlying the manifestation of mirror movements (Verstynen and Ivry 2011).…”
mentioning
confidence: 99%